Long‐term fertilization does not affect soil carbon/nitrogen/sulfur ratios or the proportion between labile and nonlabile fractions in Mollisols. Issue 3 (10th May 2020) - Liliana, Vega Jara; Gutierrez Boem, Flavio; Garcia, Fernando; Rubio, Gerardo
Abstract: Agricultural management practices such as fertilization may affect the overall soil quality and nutrient supply capacity. In this study, we hypothesized that long‐term fertilization promotes (a) an increase in the proportion of easily degradable soil organic C, N, and S fractions and (b) changes in the soil C, N, and S stoichiometric ratios in the direction of favoring the specific nutrient added to the soil. We included S in our study due to the increasing importance of S fertilization in many agricultural soils. A long‐term experiment involving six fertilization treatments and maize ( Zea mays L.), soybean [ Glycine max (L.) Merr.], and wheat ( Triticum aestivum L.) as cash crops was conducted for 14 yr in an on‐farm network located in the Pampean region (Argentina). Long‐term fertilization did not have a central role in defining the C, N, and S distribution between soil organic fractions or their stoichiometric ratios since the particulate organic matter (POM)‐C/total C, POM‐S/total S, C/N, C/N, and N/S ratios were not affected by fertilization treatments and the mineralizable N/total N ratio varied in a very short range. Instead, long‐term fertilization increased residue C inputs to the soil (8.7–19 Mg ha −1 over the unfertilized control) and, in turn, increases in soil total C, N, and S followed a linear relationship with residue inputs. This relationship was not affected by fertilization or site factors. These data contribute to understanding of the effects of continued fertilization on soil properties such as the distribution of fast‐ and slow‐cycling organic matter and nutrient concentrations, which are essential for effectively managing soils for sustainable agriculture.